A study on the executive functioning skills of Greek–English bilingual children – a nearest neighbour approach. Issue 1 (8th January 2023) - Papastergiou, Athanasia; Sanoudaki, Eirini; Tamburelli, Marco; Chondrogianni, Vasiliki
Abstract: Findings of bilingual participants outperforming their monolingual counterparts in executive functioning tasks have been repeatedly reported in the literature (Bialystok, 2017 ). However, uncontrolled factors or imperfectly matched samples might affect the reliability of these findings. This study aims to take into account a range of relevant variables in combination with innovative analyses to investigate the performance of one unstudied language group, Greek–English bilingual children in the north of England, compared to monolingual control groups. Our battery of executive function tasks taps into inhibition, updating and shifting. We use k-means nearest neighbour methods to match the groups and factor analysis to determine language proficiency. We find that bilinguals' accuracy is on a par with their monolingual peers – however, they are faster in inhibition and working memory tasks. Our study provides strong evidence for the presence of a bilingual advantage in these domains, while making important methodological contributions to the field.